The Application of the Gallery Walk Method in Increasing Student Activity in Islamic Education Learning - Nurhafsah; Zuhri, Syarifuddin; Soraya, Nyayu; Nyimas Yunierti Prihatin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This study was motivated by the low level of student engagement in Islamic Religious Education (PAI) among eighth-grade. Observations and interviews with school personnel revealed that many students tended to be passive during learning activities, mainly due to the use of conventional, teacher-centered methods that did not actively involve students. To address this issue, the researcher implemented the Gallery Walk method as an alternative instructional approach that is more interactive and student-centered. This method encourages students to work in groups, engage in discussions, express ideas, and move around the classroom to observe and reflect on the work of other groups. As a result, students are expected to become more active physically, mentally, and socially during the learning process. The study employed a quantitative approach using a one-group pretest-posttest pre-experimental design. The research subjects were 26 students from class VIII A. The instrument used was a student learning activeness questionnaire administered before and after the implementation of the Gallery Walk method. The results showed an increase in student activeness, with the average pretest score rising from 74.5 to 84.19 in the posttest. A paired sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest scores. These findings demonstrate that the Gallery Walk method is effective in enhancing student engagement in Islamic Religious Education.